Effect of ethanol solvent concentrations in pepino melon fruit (Solanum muricatum Aiton) extraction on total flavonoid, phenolic, and beta-carotene content - Girly Risma Firsty; Nining Sugihartini; Sri Mulyaningsih (Universitas Ahmad Dahlan, 2023)
The quality of an extract is determined by the type and level of compounds contained therein. The solvent is one of the elements that influences the extract's quality. Therefore, extraction must be carried out using a solvent that can extract bioactive substances. This study was aimed at obtaining the optimal concentration of ethanol in extracting flavonoids, phenolics, and beta-carotene from pepino melon fruit. In this study, dried pepino melon fruit was extracted using ethanol of 50%, 70%, and 96%. The extracts were analyzed qualitatively for phenolic and flavonoid using thin layer chromatography (TLC), and quantitatively using a spectrophotometry. Meanwhile, beta-carotene levels were determined using high pressure liquid chromatography (HPLC). The data of level flavonoid, phenolic, and beta-carotene were statistically analyzed using multivariate analysis of variance. The results showed that 50%, 70%, and 96% ethanol solvent produced extracts with a yield value of 51.8%; 87.4%; 54.6%; total flavonoid content of 0.298 ± 0.04 mgQE/g; 0.559 ± 0.03 mgQE/g; 0.289 ± 0.01 mgQE/g; total phenolic content of 4.763 ± 0.08 mgGAE/g; 3.631 ± 0.12 mgGAE/g; 3.317 ± 0.10 mgGAE/g; beta-carotene level of 0.157 ± 0.02 mg/g; 0.910 ± 0.16 mg/g; 1.054 ± 0.13 mg/g, respectively. The statistical analysis showed that there was a significant difference in different ethanol concentrations in extraction with the content of total flavonoids, total phenolics, and beta-carotene (p<0.05). The optimal ethanol solvent for extracting flavonoids, phenolic compounds, and beta-carotene from pepino melon fruit was 70% ethanol.